Cover Image, Volume 530, Issue 16. Issue 16 (14th September 2022) - Bedenbaugh, Michelle N.; Brener, Samantha C.; Maldonado, Jose; Lippert, Rachel N.; Sweeney, Patrick; Cone, Roger D.; Simerly, Richard B.
Abstract : The cover image is based on the Research Article Organization of neural systems expressing melanocortin‐3 receptors in the mouse brain: Evidence for sexual dimorphism by Michelle N. Bedenbaugh et al., https://doi.org/10.1002/cne.25379 . Image Credit: Michelle Bedenbaugh.